YOHANES 20:19-31 DAN TEOLOGI BELASKASIH - Marmidi, F.X.; Saragih, Arie Rizky Oktovianus; Surip, Stanislaus (LOGOS, 2023)
This study aims to examine whether the Gospel of John 20:19-31 contains a theology of mercy. This theology is actualized in the Catholic Church’s tradition, especially in the liturgical celebration of Divine Mercy Sunday, where it uses John 20:19-31 as the third reading in the Eucharist. The passage of John 20:19-31, in fact, does not employ the word “mercy” or “love.” It narrates the appearance of the risen Jesus to the frightened disciples. Applying synchronic and diachronic approaches to the text, this article will show that John 20:19-31 contains theologically “mercy” described in the acts of Jesus Christ: His appearance, his presence, and his forgiveness. Mercy belongs to God; it depicts the character of Jesus Christ, and it was taught by Jesus for His disciples to practice. Even though in the Church Fathers’ writings and the Ecclesiastical Documents, John 20:19-31 has been related to the theme of mercy, in this article it will be observed textually to find that it richly reflects the theology of mercy.